Synthesis and Novelty for Developing the Framework in Academic Writing - Djuwari Djuwari (Philippine Social Science Journal, 2021)
In academic writing, the authors have to cite other references as the basis of the arguments they have to assert. This citation is important in academic writing. However, writing all the statements in a research paper or article needs analyzing and synthesizing. From this activity, the authors can develop the frameworks for creating the novelty. This article attempts to explain how to quote the statements based on the references and build the framework by synthesizing and creating the novelty. First, the texts cited are rearranged and analyzed using the concept of cohesiveness and coherence. They are presented in tables to see the differences and similarities. Then, they are synthesized. Thus, all references cited are finally ended with the refined arguments as the new ideas as the novelty of the research paper. It can be inferred that by using the concept of cohesiveness and coherence, the authors of academic writing can synthesize all the citations and create novelty. The authors should create novelty by synthesizing all the references they have already cited. By doing so, the research paper—as the product of academic writing—the authors write will be eligible for publication.